Respuesta agronomica de la yuca a duracion y modalidad del almacenamiento de estacas - Leihner, D.E.; Andrade, A.S. (International Center for Tropical Agriculture, 1979)
The methodology used for better conservation of the quality of planting material and to reduce the losses caused by the inadequate storage of cuttings is discussed. Generally, it is recommendable to shorten the storage period as much as possible. General conditions for the conservation of cuttings are listed. Different systems and storage periods were evaluated using var. CMC 76. The sprouting process was faster in stored material than in fresh cuttings. Final percentage of sprouting (95-100) was not affected by storage time when this was adequate. It was concluded that: (1) The most important factor in the decrease in cassava yields due to the storage of cuttings, is their loss of sprouting ability. (2) Under adequate conditions of storage and with chemical treatment, cuttings may be conserved for several mo. (3) In tropical climates, the storage of planting material in a fresh, shaded and moderately humid environment is more favorable than in storehouses. (4) Storage conditions for cuttings are more critical, the longer it lasts. (5) In spite of conserving material under good conditions and obtaining 100 percent sprouting, yield decreases were observed due to the prolonged storage. (CIAT)